Responses of soil organic and inorganic carbon vary at different soil depths after long‐term agricultural cultivation in Northwest China. (29th April 2019) - Wang, Yugang; Jiang, Jiang; Niu, Ziru; Li, Yan; Li, Chenhua; Feng, Wenting
Abstract: Whether the dryland to cropland conversation in arid regions could lead to a decrease in soil carbon (C) and land degradation remains unclear. In this study, we investigated the vertical patterns of soil C change with different lengths of land use history in the arid regions of China and explored the controls and mechanisms of these changes. One native desert grassland and six croplands with similar management but different cultivation times (i.e., 1, 3, 5, 15, 30, and 50 years) and were selected in Xinjiang, Northwest China. We measured both soil organic and inorganic C concentrations and soil properties (e.g., total nitrogen [N], NO3 − ‐N, NH4 + ‐N, pH, and electrical conductivity) with a 20‐cm depth interval down to 2 m in all croplands. The results showed that soil organic carbon (SOC) stocks increased with cultivation year for the topsoils (0–120 cm), which could be a result of higher plant C inputs and decreased soil pH in cropland than in the native desert. Soil pH explained the largest variation (45%) of SOC concentration. Soil inorganic C (SIC) stocks decreased with cultivation year in topsoils layers (0–40 cm) but increased in deep soil layers (120–200 cm), resulting in the net increment of SIC to the depth of 200 cm. This pattern might be caused by changes in soil pH in the cropland. Overall, this study demonstrated that, instead of reducing soil C, proper management of the desert ecosystem can enhance soil C sequestration in the arid regions.